Analysis of Translation Techniques in the Article "Cyberbullying: A Digital Society Dilemma" in NADI Magazine Edition 28/2021 - Fira Lubis; Tanti Kurnia Sari (Indonesian Journal of Advanced Research, 2024)
The aim of this research is to find out common translation and classification techniques in translating the article "Cyberbullying: A Dilemma of Digital Society". This investigation is a translation investigation. Molina and Albir's theory is used to analyze translation techniques. The data for this research are articles in Indonesian and German with the title "Cyberbullying: A Dilemma in Digital Society". The data source for this research is NADI Magazine Edition 28/2021 pages 21-27. Data analysis in this research used qualitative descriptive methods. The translation techniques used were: adaptation with two sentences (0.88%), strengthening with one sentence (0.44%), borrowing with 33 sentences (14.53%), compensation with 20 sentences (8.81%), general equivalent with 14 sentences (6.16%). ), generalization with five sentences (2.20%), linguistic reinforcement with 32 sentences (14.09%), literal translation with seven sentences (3.08%), modulation with 26 sentences (11.45%), specification with five sentences (2.20%), reduction with 27 sentences (11.89%), transposition with 55 sentences (24.27). This translation technique is divided into six types, namely: couplet technique with six sentences (10.17%), triplet technique with 19 sentences (32.20), quartet technique with 19 sentences (32.20), quintet technique with eight movements ( 13.56%), sextet technique with six movements (10.17%), and septet technique with one movement (1.70%). There are two most common classifications, namely the triplet technique with 19 movements (32.20), the quartet technique with 19 movements (32.20). The translation results are then validated by experts. Expert assessment of the quality of the translation is good.